Level of Population’s Satisfaction with Quality of Life Indicators in Krasnoyarsk - I. V. Sergeeva; A. A. Lang; R. O. Morozov; A. Yu. Senchenko (Здоровье мегаполиса)
Background. The large city of Krasnoyarsk represents a unique urban environment where various indicators, such as ecology, infrastructure, healthcare, and education services, play an important role in shaping the level of residents’ satisfaction and impacting their quality of life.Purpose: To study the level of the population’s satisfaction with the quality of life indicators in Krasnoyarsk.Material and methods. A sociological survey was conducted using a questionnaire. The authors also applied the random sampling technique. The sample size was 687 respondents.Results. The study identified several key problems: low levels of satisfaction with environmental quality, quality of medical services, and accessibility of healthcare organizations; low income of the population; limited opportunities for recreation and entertainment. Overall, the study highlights the importance of further studying and improving quality of life indicators in Krasnoyarsk to increase residents' satisfaction and create a more comfortable urban environment.Conclusion. Based on the level of the population’s satisfaction, it is possible to consider public opinion in management decision-making and developing social programs for urban infrastructure planning.